Innovative Water Management at the Environmental Campus Birkenfeld - Helling, Klaus; Bölsche, Dorit Schumann (Universitas Diponegoro, 2021)
Sustainable water management has a high relevance for universities and this paper describes the innovative water management system at the Environmental Campus Birkenfeld (ECB), which belongs to Trier University of Applied Sciences. The ECB is called the